Rosie's Race - Lapage, Ginny (Collins Educational)
In this book rosie and jack were happy. when they joined the sport center. it was great fun, there was lots to do. and rosie did not feel lonely again. because she could join in with the other children.
Keywords: Juvenile literature-Children-Fiction